Sustainable Perspective of Electric Vehicles and Its Future Prospects - Maske, Pawan; Chel, Prof. Arvind; Goyal, Pradeep K.; Kaushik, Dr. Geetanjali (Journal of Sustainable Materials Processing and Management, 2021)
Vehicles running on fossil fuel are creating a threat to the environment by emitting pollutants such as carbon monoxide, carbon dioxide and sulfur and nitrogen oxides into the environment. Electric vehicles and hybrid electric vehicles provide a perennial solution to this problem and since the utilization of renewables for charging, the market is on verge of electric vehicle revolution. Electric propulsion systems can also be used in heavy transport vehicles, thus transitioning them to electric. This paper puts forth an overview of the electric vehicles for transportation of masses and freight across the globe and emphasis on the battery charging infrastructures. Recent trends and advancements in electric vehicle batteries are discussed briefly, along with sustainability in Li-ion batteries and its materials; moreover, a comparative study of different electric vehicles available in the Indian market is done. Similarly, the incentives offered by government, challenges faced by these vehicles and future development areas are conversed at the end of the paper.